2014
DOI: 10.1177/0734242x13518959
|View full text |Cite
|
Sign up to set email alerts
|

Physical, mechanical and hydration kinetics of particleboards manufactured with woody biomass (Cupressus lusitanica, Gmelina arborea, Tectona grandis), agricultural resources, and Tetra Pak packages

Abstract: Lignocellulosic wastes resulting from agricultural activities as well as Tetra Pak residues from urban centres can cause significant levels of pollution. A possible action to minimize this problem is to use them in the production of particleboards. The purpose of this study was to evaluate the physical, mechanical, and hydration properties of particleboards manufactured with the mixture of woody biomass (Cupressus lusitanica, Gmelina arborea, and Tectona grandis) and either agricultural wastes [pineapple leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, variation in Consumption pellet is affected by other characteristics of the pellets. Although in this study no physical nor chemical characteristics of the pellets were reported, in previous works these properties have been included [18][19][20] variation in length, density (of pellet and bulk density) and the dimensions of the particles forming the pellet were demonstrated. Carvalho et al [16] indicate that these pellet properties affect how they are fed into the domestic stove system when a screw feeder is employed.…”
Section: Consumption Pellet Flue Ash Characterisation and Temperaturesmentioning
confidence: 89%
See 2 more Smart Citations
“…However, variation in Consumption pellet is affected by other characteristics of the pellets. Although in this study no physical nor chemical characteristics of the pellets were reported, in previous works these properties have been included [18][19][20] variation in length, density (of pellet and bulk density) and the dimensions of the particles forming the pellet were demonstrated. Carvalho et al [16] indicate that these pellet properties affect how they are fed into the domestic stove system when a screw feeder is employed.…”
Section: Consumption Pellet Flue Ash Characterisation and Temperaturesmentioning
confidence: 89%
“…Presently, the technological adaptations to the pellet production process are known for many tropical-climate agricultural crops [18], as are the evaluation of some aspects of the pellet quality and the information about the physical, chemical or energetic characterisation [19,20]. However, the behaviour of these crops in equipment such as domestic pellet stoves, regarding energy efficiency and level of emissions are scarcely known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] The aim of this study is to develop and evaluate a novel sandwich structure ( Figure 1) using a lightweight and relatively thick core materials in form of particleboard panels from local and cheap lignocellulosic resources attaching to two thin, and stiff woven fabric skins using VARTM technique to construct high performance structure for use in various technical applications. Huge efforts are being intensified to elaborate their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of this form of post‐consumer packaging is more difficult than that of traditional packaging made of a single material, so in past decades the majority of this waste packaging was burned or dumped as landfill, causing environmental pollution and waste of resources . Today, owing to the lack of material such as wood, oil and non‐ferrous metal resources, post‐consumed paper/Al foil/PE composites have higher recycling value …”
Section: Introductionmentioning
confidence: 99%